Pengaruh Integritas, Profesionalisme Badan Pengawas Dan Ketaatan Aturan Akuntansi Pada Pengelolaan Keuangan Dalam Pencegahan Fraud Di Lembaga Pengkreditan Desa Kabupaten Buleleng - Putu Wanda Aristayanti; Nyoman Ari Surya Dharmawan (Universitas Pendidikan Ganesha, 2025)
Village Credit Institutions play a vital role in providing financial access to rural communities, yet they are susceptible to fraud, which negatively impacts their finances and diminishes public trust. Instances of fraud in Village Credit Institutions, such as financial data manipulation and fund misuse, pose serious challenges to local economic development. Integrity, professionalism of supervisors, and adherence to accounting regulations are three key factors that can influence the prevention of fraud in these institutions. This study aims to identify the impact of integrity, the professionalism of supervisory bodies, and adherence to accounting regulations in preventing fraud. This research is quantitative with a causal approach. Using the Slovin technique, a sample of 50 Village Credit Institutions from various districts was obtained and analyzed using SPSS. The results indicate that integrity, the professionalism of supervisory bodies, and adherence to accounting regulations positively and significantly affect fraud prevention.